2015
DOI: 10.1007/s10661-015-4622-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and molecular effects of di-n-butyl phthalate (DBP) on CYP1A, SOD, and GPx in Cyprinus carpio (common carp)

Abstract: Di-n-butyl phthalate (DBP), a widely used plasticizer in the plastic industry, affects regulation of the endocrine system and causes toxicity in animals. In the present study, we evaluated a series of ecotoxicological stress biomarkers in the common carp (Cyprinus carpio) as an experimental model to test for alterations in gene expression at a sublethal concentration of 1 mg/L DBP for 4, 24, and 96 h. In gills, an immediate increase in CYP1A messenger RNA (mRNA) levels was observed within the first 4 h and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 42 publications
3
3
0
Order By: Relevance
“…The depressed CYP1A expression can be related to toxicant mediated inhibition of the gene activity [12]. Later, Dhamgaye et al [62] have reported MG as a substrate for CYP1A and credited the xenobiotic metabolism of MG into Leuco-MG (LMG) [63,64]. This LMG is accumulated in the tissues in conformity to present findings, illustrating the enhanced and prolonged MG toxicity.…”
Section: Discussionsupporting
confidence: 83%
“…The depressed CYP1A expression can be related to toxicant mediated inhibition of the gene activity [12]. Later, Dhamgaye et al [62] have reported MG as a substrate for CYP1A and credited the xenobiotic metabolism of MG into Leuco-MG (LMG) [63,64]. This LMG is accumulated in the tissues in conformity to present findings, illustrating the enhanced and prolonged MG toxicity.…”
Section: Discussionsupporting
confidence: 83%
“…Differences in enzy me activity can be interpreted to accumulat ion of the OCPs and the other many xenobiotics on sediment and also in fish tissues. Similar studies with our study were done in terms of enzyme act ivity changes for carp in Turkey (Ozmen et al 2006;Gungordu and Ozmen 2011;Karaca et al 2014;Agus et al 2015).…”
Section: Resultssupporting
confidence: 86%
“…For all three tested compounds, we were able to establish dose-response relationships between each single locomotion variable and the toxicant exposure gradient. The observed behavioural changes were in line with previously published sublethal toxicity margins [71][72][73][74]. The observed toxicant-induced locomotive disturbances support the use of locomotion-based endpoints for sublethal toxicity screening.…”
Section: Discussionsupporting
confidence: 89%